2009
DOI: 10.1111/j.1399-3054.2009.01220.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene and salicylic acid control glutathione biosynthesis in ozone‐exposed Arabidopsis thaliana

Abstract: Ozone produces reactive oxygen species and induces the synthesis of phytohormones, including ethylene and salicylic acid. These phytohormones act as signal molecules that enhance cell death in response to ozone exposure. However, some studies have shown that ethylene and salicylic acid can instead decrease the magnitude of ozone-induced cell death. Therefore, we studied the defensive roles of ethylene and salicylic acid against ozone. Unlike the wild-type, Col-0, Arabidopsis mutants deficient in ethylene signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
52
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(60 citation statements)
references
References 72 publications
8
52
0
Order By: Relevance
“…3,38 Integration of SA and JA signaling has been demonstrated 39 and SA reported to increase de novo biosynthesis of GSH. 40 In our studies, the ratio of GSH/GSSG was observed to be more in leaf and fruit than root tissues. In parallel with our observations, imbalances in GHS/GSSG ratio were reported when plants were exposed to oxidative stress.…”
Section: Redox Statussupporting
confidence: 49%
“…3,38 Integration of SA and JA signaling has been demonstrated 39 and SA reported to increase de novo biosynthesis of GSH. 40 In our studies, the ratio of GSH/GSSG was observed to be more in leaf and fruit than root tissues. In parallel with our observations, imbalances in GHS/GSSG ratio were reported when plants were exposed to oxidative stress.…”
Section: Redox Statussupporting
confidence: 49%
“…Particularly interesting is the finding that GSH induced expression of ICS1 and SARD1 in an AtGLR3.3-dependent manner, two essential genes for SA biosynthesis (Wildermuth et al, 2001;Zhang et al, 2010). A regulatory role for SA in GSH production in plants has been described (Srivastava and Dwivedi, 1998;Yoshida et al, 2009). Our finding that GSH can strongly induce ICS1 expression (Table I) implies that there is a positive AtGLR3.3-dependent feedback mechanism for GSH to enhance SA biosynthesis under stress conditions.…”
Section: Gsh-mediated Atglr33-dependent Early Transcription Responsementioning
confidence: 52%
“…However, additional evidence suggests that in addition to recycling the Met moieties via the Yang cycle, the de novo synthesis of Met is required when high rates of ethylene production are induced. 79 Moreover, S availability and ethylene have been shown to regulate GSH synthesis and stress tolerance to ozone 80 and Cd 81,82 stress. Glutathione acts as a storage and transport form for Cys; otherwise the excess Cys present in the cell becomes toxic.…”
Section: Ethylene Cross-talk Associated With Sulfurmentioning
confidence: 99%